Pandangan MUI Langkat terhadap Budaya Tabur Bunga di Atas Perahu Baru yang Akan Pergi Melaut: Studi Kasus di Pelabuhan Sei Bilah Pangkalan Brandan - Muhammad Refli Reynaldi; Muhammad Saleh; Diyan Yusri (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Based on the results of observations at the research location, the identification of the problems found was obtained, namely: The implementation of the flower sowing culture in the coastal areas of Langkat Regency is still carried out precisely as a cultural tradition. Communities who carry out the sea jamu ritual do not yet have a qualified understanding of religion. So that the implementation of the sea herbal ritual is considered a tradition in the Malay tribe which is still preserved without regard to the legal lines in Islamic religious teachings. The results of these observations are used by the authors as a basis for formulating the problem in this study, namely how is the compatibility between culture and Islamic law regarding the implementation of sowing flowers in the Langkat Regency area? The research method used is a qualitative research method, namely the author collects data through data collection techniques in a theoretical description and facts in the field based on observations, interviews and documentation so that the results of the implementation of this research are: Efforts to standardize the sea alms ceremony tradition from elements elements prohibited by Islam, one of which is the use of offerings in the form of various kinds of food and buffalo heads or goat heads, namely by providing enlightenment to the community little by little, slowly and gradually, as was done by the scholars and religious leaders in Sei Blade. It is different from the sea alms ceremony in Sei Bilah because the community has a strong belief in things like that. In the procession of the sea alms ceremony in Sei Bilah, the ritual of burning incense and believing in the myth of the existence of sea guardians.